FUNGSI PEMERINTAH KECAMATAN BOJONGSOANG DALAM MENGURANGI RESIKO DAN MITIGASI BENCANA BANJIR PADA KAWASAN PEMUKIMAN DI KABUPATEN BANDUNG TAHUN 2024 - Ragawilafa, Ariel; Mahendra, Medi (JISIPOL | Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to examine the role of the Bojongsoang Subdistrict Government in disaster risk reduction and mitigation efforts in the residential areas of Bojongsoang Subdistrict, Bandung Regency, in 2024. The background of this study is the high frequency of disasters, particularly floods, which have a significant impact on the safety and welfare of the community. The research uses a qualitative method with an explanatory case study approach. Data were obtained through purposive sampling techniques involving interviews, observation, and documentation. The results show that the government's service function in disaster mitigation is working quite well through the provision of an early warning system, the construction of flood control infrastructure, and coordination with relevant agencies. However, community empowerment functions are still constrained by limited infrastructure and uneven participation. Community awareness of disaster risk reduction efforts is growing but is not yet optimal. The study concludes that improving the quality of services and community empowerment needs to be done simultaneously to strengthen a sustainable disaster mitigation system. The recommendations proposed include strengthening the early warning system, improving mitigation facilities, and educating and raising public awareness about disasters. Optimizing these two functions is expected to create a safer and more resilient residential environment in the face of disasters.